Strategi Komunikasi Pemasaran Digital Brand Fashion Melalui Media Sosial Instagram - Pranasakya Ananda Gilang Umbara; Rini Rinawati (Bandung Conference Series: Communication Management, 2023)
Abstract. This research is entitled Digital Marketing Communication Strategy for Fashion Brands Through Instagram Social Media (Case Study on Instagram Brand @fabricthejeans). The purpose of this research is to find out the marketing communication strategy carried out by Fabric The Jeans through Instagram and the Instagram features used for marketing on Instagam. The subjects of this research are the founder and owner of Fabric The Jeans, marketing and admin of Instagram Fabric The Jeans, and followers of the Instagram account Fabric The Jeans. The data collection techniques of this research were observation and interviews. Data analysis techniques used in this research are data reduction, data presentation, verification and conclusion drawing. The results of this study are market segmentation conducted by Fabric The Jeans based on demographics, namely among teenagers aged between 16 years to 24 years with a male-only market. Segmentation based on geography or region, namely Bandung, Jakarta, Bekasi, and Cianjur. There are also countries such as Indonesia, Malaysia, Germany, and the United States. Segmentation based on psychographics, namely people who are in style with denim. Fabric The Jeans target market in general is people who have an interest in the metal music genre and extreme sports such as skateboarding and bmx. The specific target market determined by Fabric The Jeans is motorcycle children, especially custom motorcycles. Fabric The Jeans wants to position itself as a specialist motorcycle denim brand by producing basic casual style products and carrying navy or dark blue colors in every Instagram upload that is close to indigo color as the basic color of denim fabric. The reason why Fabric The Jeans conducts digital marketing communications on Instagram is because it is free and easy to use because it only has photos and videos using the feeds and insta story features which are uploaded two to three times in one day, has many users, one of which is children. young people or teenagers, can connect with other social media such as Facebook and can display links to other platforms such as WhatsApp, Tokopedia, and Shopee. Abstrak. Penelitian ini berjudul Strategi Komunikasi Pemasaran Digital Brand Fashion Melalui Media Sosial Instagram (Studi Kasus Pada Instagram Brand @fabricthejeans). Tujuan dilakukannya penelitian ini adalah untuk mengetahui segmentasi pasar, target pasar, dan positioning Fabric The Jeans melalui Instagram. Subjek penelitian ini adalah pendiri sekaligus pemilik Fabric The Jeans. Teknik pengumpulan data penelitian ini adalah observasi dan wawancara. Teknik analisis data yang digunakan dalam penelitian ini adalah reduksi data, penyajian data, verifikasi dan penarikan kesimpulan. Hasil penelitian ini adalah segmentasi pasar yang dilakukan Fabric The Jeans berdasarkan demografis yaitu kalangan anak remaja rentang usia antara 16 tahun hingga 24 tahun dan khusus laki-laki. Segmentasi berdasarkan geografis atau wilayah yaitu Kota Bandung, Jakarta, Bekasi, dan Cianjur. Juga ada negara Indonesia, Malaysia, Jerman, dan Amerika Serikat. Target pasar Fabric The Jeans secara umum yaitu orang yang memiliki ketertarikan di bidang musik bergenre metal dan cabang olahraga ekstrim seperti skateboard dan bmx. Target pasar khusus yang ditentukan oleh Fabric The Jeans yaitu kalangan anak motor terutama motor custom, semi trail, dan adventure. Segmentasi berdasarkan psikografis yaitu orang yang senang bergaya dengan denim. Fabric The Jeans ingin memposisikan dirinya sebagai brand denim motor specialist dengan menghasilkan produk bergaya basic casual dan menampilkan feeds dengan warna navy atau biru tua di setiap unggahan Instagramnya yang mendekati warna indigo sebagai warna dasar kain denim. Alasan mengapa Fabric The Jeans melakukan komunikasi pemasaran digital di Instagram dikarenakan pemakaiannya yang gratis dan mudah dalam penggunaannya karena hanya bermodal foto dan video menggunakan fitur feeds dan insta story yang dilakukan dua hingga tiga kali unggahan dalam satu hari, memiliki banyak pengguna yang salah satunya kalangan anak muda atau remaja, bisa terhubung dengan media sosial lainnya seperti facebook dan bisa menampilkan tautan platform lain seperti whatsapp, tokopedia, dan shopee.